2022
DOI: 10.3390/insects13040323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Agro-Industrial Byproduct-Based Diets on the Growth Performance, Digestibility, Nutritional and Microbiota Composition of Mealworm (Tenebrio molitor L.)

Abstract: The aim of this study was to evaluate the effects of agro-industrial byproduct-based diets on the productive parameters, digestibility, insect composition, and gut microbiota of mealworm (Tenebrio molitor) larvae. Three formulations corresponding to three different levels of starch and protein were tested: one formulation based on bread remains and brewer’s yeast, representing a diet of high starch (61.1%) and low crude protein (18.5%) (HS-LP); and two formulations in which an additional four byproducts (courg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…Previous studies have demonstrated that Tenericutes are directly associated with metabolism, and hosts with a high abundance of Tenericutes exhibit increased insulin sensitivity (Yuan et al, 2021 ). Consequently, their high concentration is helpful for the nutrient intake of larvae, and this phenomenon has been documented in other insects (Montalban et al, 2022 ). By comparison, the ability to use diversified food is an effective way to increase the survival rate for adult wasps.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous studies have demonstrated that Tenericutes are directly associated with metabolism, and hosts with a high abundance of Tenericutes exhibit increased insulin sensitivity (Yuan et al, 2021 ). Consequently, their high concentration is helpful for the nutrient intake of larvae, and this phenomenon has been documented in other insects (Montalban et al, 2022 ). By comparison, the ability to use diversified food is an effective way to increase the survival rate for adult wasps.…”
Section: Discussionmentioning
confidence: 81%
“…Consequently, their high concentration is helpful for the nutrient intake of larvae, and this phenomenon has been documented in other insects (Montalban et al, 2022). By comparison, the ability to use diversified food is an effective way to increase the survival rate for adult wasps.…”
Section: Discussionmentioning
confidence: 95%
“…As has been observed in previous studies, genus abundance also depends on the diet composition provided. Indeed, in larvae fed a higher dietary protein content, the presence of species able to produce cellulolytic enzymes, such as Acinetobacter spp., was reduced ( 63 ). In our study, larvae fed the WB diet showed differences in microbial OTU abundance, resulting in higher loads of Pediococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Based on several recent studies on the taxonomic profiling of insects destined for food or animal feed, the dominant microbial groups are summarized in Table 4 . In all observed insect species, the highest abundant phyla of gut bacteria generally belonged to Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes [ [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] ]. Regarding the BSF, considered the most efficient biowaste-converting insect species, IJdema et al.…”
Section: Agri-food Waste Utilizing Insects and Gut Symbiotic Microbiotamentioning
confidence: 99%